Pemikiran Husein Muhammad Tentang Relasi Suami Isteri Perspektif Gender - Muchtar Wahyudi Pamungkas; Miftahul Huda; Rohmah Maulidia (Journal of Economics, Law, and Humanities, 2024)
This research was motivated by differences of opinion between the fuqaha and Kiai Husein regarding husband-wife relations. Kiai Husein synchronized the postulates of jurisprudence in solving contemporary development problems using the theory of gender equality. This research includes research that explores data by interviewing related figures and extracting data from his works, known as library research. The findings show that kiai Husein Muhammad's gender equality does not come from gender, whether from women or men. Still, gender is the difference between men and women, which is created by themselves, not by God or the potential that each individual can create.